Ten-year kidney transplant survival of cyclosporine- or tacrolimus-treated patients in Brazil. Issue 7 (2nd July 2016) - Gomes, Rosângela Maria; Guerra Júnior, Augusto Afonso; Lemos, Lívia Lovato Pires de; Costa, Juliana de Oliveira; Almeida, Alessandra Maciel; Alvares, Juliana; Filho, Charles Simão; Cherchiglia, Mariângela Leal; Andrade, Eli Iola Gurgel; Godman, Brian; Acurcio, Francisco Assis
ABSTRACT: Background : Cyclosporine and tacrolimus are well established immunosuppressants; however little is known about long term survival rates. The project aim was to compare 10-year graft survival and associated factors among kidney transplant patients within the Brazilian Public Health System (SUS) prescribed either immunosuppressant. Methods : Analyze a national cohort of kidney transplant recipients within SUS. Graft loss defined by death or dialysis for more than three months. Kaplan-Meier method used to estimate cumulative probabilities of survival. Cox proportional hazards model used to evaluate factors associated with progression to graft loss. Results : 13, 811 patients were included, 5, 887 used cyclosporine and 7, 924 tacrolimus. A higher risk of graft loss was associated with tacrolimus, a deceased donor, additional years of age, median period of dialysis greater than 47 months, diagnosis of diabetes as the primary cause of chronic kidney disease and transplantation between 2005 and 2009. Conclusions : Among other factors, tacrolimus-based regimens were associated with worse graft survival.